The trouble with theory the educational costs of postmodernism - Kitching, Gavin (Allen & Unwin, 2008)
"A critique of postmodernism and poststructuralism and an examination of their impact on higher education. Argues that students influenced by these trends in philosophy produce radically incoherent ideas about language, meaning, truth, and reality"--Provided by publisher.